Pemberdayaan Siswa Sekolah Dasar melalui Penerapan Model Cara Belajar Obat yang Benar untuk Meningkatkan Literasi Obat Sejak Dini - Syofyan Syofyan; Dachriyanus Dachriyanus; Noviatri Noviatri (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2025)
The use of medicines is common among adults; however, for children, medication is often considered unfamiliar because their knowledge of the benefits and risks of medicines remains limited. Therefore, early education about medicines is essential to build proper awareness and encourage children to become agents of change in promoting the rational use of medicines within their families and communities. This community service activity aimed to improve medication literacy and awareness of rational medicine use among elementary school students through the Correct Medicines Learning Model (CBOB). The program was implemented in six stages: (1) socialization with partners, including teachers, students, and parents; (2) training of junior pharmacists for fifth-grade students; (3) application of science and technology through the CBOB model; (4) post-activity mentoring; (5) evaluation; and (6) sustainability. The evaluation phase specifically used pre-tests and post-tests to assess students’ knowledge, perceptions, attitudes, and behaviors. The results showed an increase in knowledge scores from 53.5 to 63.4, perceptions from 37.7 to 49.4, and attitudes from 67.9 to 71.6, while behavior remained stable at 69.3. In addition, the Little Pharmacist Community, School Medicinal Plants (TOS), and Apotekids Corner were established as tangible outputs of the program. In conclusion, the CBOB model effectively enhanced students’ understanding and awareness of rational medicine use and has the potential to be developed as a sustainable, school-based medicine education model.